Structural insight into the catalytic mechanism of a cis-epoxysuccinate hydrolase producing enantiomerically pure d(−)-tartaric acid. Issue 61 (13th July 2018) - Dong, Sheng; Liu, Xi; Cui, Gu-Zhen; Cui, Qiu; Wang, Xinquan; Feng, Yingang
Abstract : The catalytic mechanism for the high stereoselectivity and product enantioselectivity of a cis -epoxysuccinate hydrolase producingd (−)-tartaric acids was elucidated. Abstract : Crystal structure determination and mutagenesis analysis of a cis -epoxysuccinate hydrolase which produces enantiomerically pured (−)-tartaric acids revealed a zinc ion and essential residues in the stereoselective mechanism for the catalytic reaction of the small mirror symmetric substrate.